Industrial performance of a new lubricant for manufacturing PM gears. Issue 3 (May 2016) - Sokolowski, Peter; Milbrath, Andreas; Vitti, Davide; Fontana, Stefano
Abstract : Admixed lubricants used in Powder Metallurgy (PM) have been effective at meeting the needs of the industry to manufacture traditional PM parts. With increasing demand to improve upon part tolerances, surface finish, density distribution, weight consistency, and reduced environmental impact; parts makers desire to replace traditional lubricants such as Acrawax and Kenolube. In an effort to do so, AncorLube has been developed as an engineered lubricant system to enable robust part manufacturing. This work compares the production characteristics, based on lubricant type, for a water pump gear pressed to a density of 6.80 g/cm 3 . The weight consistency was evaluated during serial production of more than 5000 gears, each weighing approximately 191 grams. A standard deviation of 0.6 grams was measured, indicating that a stable process was achieved with a premix containing AncorLube. Metallographic inspection of surface quality and density distribution was evaluated and compared against parts made with Kenolube. In addition, laboratory studies show improved ejection characteristics are obtained at typical press operating temperatures approaching 60°C (140°F).